Portraits on the crack user built by the media - Cristine Moraes Roos; Nathália Duarte Bard; Aline da Silva Basso; Agnes Olschowsky; Leandro Barbosa de Pinho
ABSTRACT Objective: evaluate how the crack user is portrayed by the media. Method: qualitative study, using fourth generation evaluation. The data were collected in interviews and field observations in a mental health network service of the Porto Alegre-RS metropolitan area. The participants were 10 users, 11 family members, 08 health service professionals and 07 managers. Results: the findings revealed that media relates the crack user profile to violence, crime and disease, which does not correspond to the reality experienced in the health service. This image disregards the different ways of using the drug and the different productions of life of these individuals, increasing social exclusion and stigma. Final considerations: The challenge is to build shared, integrated, clear and honest information.